Adsorption characteristics of H2S, SO2, SO2F2, SOF2, and N2 on NiO–MoSe2 monolayer for gas-sensing applications. (November 2021) - Hu, Xiaoyan; Gui, Yingang; Liu, Yujie; Xu, Lingna; Ran, Liang; Chen, Xianping
Abstract: Gas insulated switchgear (GIS) is an important equipment in the power transmission and distribution system, which commonly fills with SF6 /N2 insulating gas mixture. Due to the partial discharge in GIS, SF6 gas is likely to ionize and react with impurities inside the GIS, and produces SO2, H2 S, SO2 F2, and SOF2 characteristic gases. This work was devoted to detect the partial discharge by exploring new gas-sensing materials for characteristic gases detection. First, four possible modification sites of NiO on MoSe2 surface were built and optimized, it was found that the B2 site modification was the most stable one. Then, the optimal adsorption structure was obtained by analyzing the adsorption structures of gases on NiO–MoSe2 with different initial positions. Finally, the adsorption mechanism and gas-sensing characteristics were studied based on the density of state theory and molecular orbital theory. The results show that NiO doping greatly enhances the surface activity of MoSe2 for gas adsorption. The order of adsorption ability is H2 S > SO2 > SOF2 > N2 > SO2 F2, and the moderate adsorption energy indicates that NiO–MoSe2 could be a suitable gas-sensing material, which lays a theoretical foundation for the design of NiO–MoSe2 sensors. This research provides a new method to ensure the stability of GIS operation. Highlights: It is the first time to use NiO–MoSe2 as a gas-sensing material for H2 S, SO2, SO2 F2, SOF2 and N2 . Comprehensive analysis reveal that the adsorption effect is H2 S > SO2 > SOF2 > N2 > SO2 F2 . This study lays a theoretical basis for developing NiO–MoSe2 based gas sensor.